Dimethylsulphoniopropionate as a water quality indicator of coral bleaching: Implications for monitoring studies on the Great Barrier Reef. (March 2021) - Fischer, Esther; Jones, Graham
Abstract: Short term stress experiments with dissolved inorganic phosphorus (DIP) and tripolyphosphate (TPP) have been carried out on the staghorn coral Acropora intermedia, collected from Heron Island in the southern Great Barrier Reef, at low and elevated seawater temperatures. Zooxanthellae, chlorophyll a, intracellular and tissue dimethylsulfoniopropionate (DMSP), and extracellular DMSP production were measured to assess the level of stress on A. intermedia at different winter and summer seasons from 2001 to 2003. Whilst no significant changes were measured in these stress indicators in 2001 and 2003, significant changes occurred in winter 2002, reflecting natural stresses on A. intermedia in the field, and stress from added DIP and TPP at high seawater temperatures. These stresses caused corals to bleach, whilst extracellular DMSP, intracellular and tissue DMSP concentrations increased, reflecting the antioxidant role of DMSP in the coral zooxanthellae and coral host to combat stress. These results have important implications for future research in the GBR. Highlights: DMSP production from A. intermedia and stressed with DIP did not change upto 10 µM (63 x reef seawater concentrations). DMSP production from A. intermedia in winter 2002 reached some of the highest levels measured. During phosphorus and heat stress DMSP forms DMS which decreases oxygen free radicals which lead to coral bleaching. High tissue DMSP in A. intermedia reflects a change of clade of zooxanthellae. A change of clade affects atmospheric DMS production from GBR corals, decreasing low level cloud over the GBR.